Descriptive Analysis of a Staff Injury-Reduction Intervention in a Human Services Setting for Children and Youth With Intellectual and Developmental Disabilities. (September 2013) - Luiselli, James K.
Clinical safety is a dominant concern for human services organizations serving people with intellectual and developmental disabilities (IDD) and high-risk challenging behaviors. This article is a descriptive analysis of components that comprised an injury-reduction intervention among direct-care staff at a specialized school. Using a behavior-based safety approach, intervention was associated with fewer staff injuries and more weeks without injury reports. The article focuses on systems-level strategies and recommendations for future research and practice.